Avian cholera in a southern giant petrel (Macronectes giganteus) from Antarctica - Leotta, Gerardo Aníbal (2003)
A southern giant petrel (Macronectes giganteus) was found dead at Potter Peninsula, King George Island, South Shetland, Antarctica. The adult male was discovered approximately 48 hr after death. Macroscopic and microscopic lesions were compatible with avian cholera and the bacterium Pasteurella multocida subsp. gallicida, serotype A1 was isolated from lung, heart, liver, pericardial sac, and air sacs. In addition, Escherichia coli was isolated from pericardial sac and air sacs. This is the first known report of avian cholera in a southern giant petrel in Antarctica.